Synthesis of amorphous and graphitized porous nitrogen-doped carbon spheres as oxygen reduction reaction catalysts - Wassner, Maximilian; Eckardt, Markus; Reyer, Andreas; Diemant, Thomas; Elsaesser, Michael S.; Behm, R. Jürgen; Hüsing, Nicola (Beilstein Journal of Nanotechnology, 2020)
Amorphous and graphitized nitrogen-doped (N-doped) carbon spheres are investigated as structurally well-defined model systems to gain a deeper understanding of the relationship between synthesis, structure, and their activity in the oxygen reduction reaction (ORR). N-doped carbon spheres were synthesized by hydrothermal treatment of a glucose solution yielding carbon spheres with sizes of 330 ± 50 nm, followed by nitrogen doping via heat treatment in ammonia atmosphere. The influence of a) varying the nitrogen doping temperature (550–1000 °C) and b) of a catalytic graphitization prior to nitrogen doping on the carbon sphere morphology, structure, elemental composition, N bonding configuration as well as porosity is investigated in detail. For the N-doped carbon spheres, the maximum nitrogen content was found at a doping temperature of 700 °C, with a decrease of the N content for higher temperatures. The overall nitrogen content of the graphitized N-doped carbon spheres is lower than that of the amorphous carbon spheres, however, also the microporosity decreases strongly with graphitization. Comparison with the electrocatalytic behavior in the ORR shows that in addition to the N-doping, the microporosity of the materials is critical for an efficient ORR.
Keywords: amorphous carbon; graphitized carbon; hydrothermal carbonization; nitridation; nitrogen doping; oxygen reduction reaction (ORR); porosity

(untitled) - Gong, K.; Du, F.; Xia, Z.; Durstock, M.; Dai, L. (Science, 2009)

(untitled) - Liu, Z.-W.; Peng, F.; Wang, H.-J.; Yu, H.; Zheng, W.-X.; Yang, J. (Angew. Chem., Int. Ed., 2011)

(untitled) - Liu, J.; Song, P.; Ning, Z.; Xu, W. (Electrocatalysis, 2015)

(untitled) - Wang, D.-W.; Su, D. (Energy Environ. Sci., 2014)

(untitled) - Yang, L.; Jiang, S.; Zhao, Y.; Zhu, L.; Chen, S.; Wang, X.; Wu, Q.; Ma, J.; Ma, Y.; Hu, Z. (Angew. Chem., Int. Ed., 2011)

(untitled) - Yang, Z.; Nie, H.; Chen, X.; Chen, X.; Huang, S. (J. Power Sources, 2013)

(untitled) - Daems, N.; Sheng, X.; Vankelecom, I. F. J.; Pescarmona, P. P. (J. Mater. Chem. A, 2014)

(untitled) - Lee, W. J.; Maiti, U. N.; Lee, J. M.; Lim, J.; Han, T. H.; Kim, S. O. (Chem. Commun., 2014)

(untitled) - Wei, Q.; Tong, X.; Zhang, G.; Qiao, J.; Gong, Q.; Sun, S. (Catalysts, 2015)

(untitled) - Inagaki, M.; Toyoda, M.; Soneda, Y.; Morishita, T. (Carbon, 2018)

(untitled) - Zhu, C.; Li, H.; Fu, S.; Du, D.; Lin, Y. (Chem. Soc. Rev., 2016)

(untitled) - Li, Y.; Zhou, W.; Wang, H.; Xie, L.; Liang, Y.; Wei, F.; Idrobo, J.-C.; Pennycook, S. J.; Dai, H. (Nat. Nanotechnol., 2012)

(untitled) - Ai, K.; Liu, Y.; Ruan, C.; Lu, L.; Lu, G. M. (Adv. Mater. (Weinheim, Ger.), 2013)

(untitled) - Yang, T.; Liu, J.; Zhou, R.; Chen, Z.; Xu, H.; Qiao, S. Z.; Monteiro, M. J. (J. Mater. Chem. A, 2014)

(untitled) - Zheng, Y.; Jiao, Y.; Chen, J.; Liu, J.; Liang, J.; Du, A.; Zhang, W.; Zhu, Z.; Smith, S. C.; Jaroniec, M.; Lu, G. Q.; Qiao, S. Z. (J. Am. Chem. Soc., 2011)

(untitled) - Guo, D.; Shibuya, R.; Akiba, C.; Saji, S.; Kondo, T.; Nakamura, J. (Science, 2016)

(untitled) - Geng, D.; Chen, Y.; Chen, Y.; Li, Y.; Li, R.; Sun, X.; Ye, S.; Knights, S. (Energy Environ. Sci., 2011)

(untitled) - Lai, L.; Potts, J. R.; Zhan, D.; Wang, L.; Poh, C. K.; Tang, C.; Gong, H.; Shen, Z.; Lin, J.; Ruoff, R. S. (Energy Environ. Sci., 2012)

(untitled) - Liu, R.; Wu, D.; Feng, X.; Müllen, K. (Angew. Chem., Int. Ed., 2010)

(untitled) - Sharifi, T.; Hu, G.; Jia, X.; Wågberg, T. (ACS Nano, 2012)

(untitled) - Wu, K.-H.; Wang, D.-W.; Su, D.-S.; Gentle, I. R. (ChemSusChem, 2015)

(untitled) - Ding, W.; Wei, Z.; Chen, S.; Qi, X.; Yang, T.; Hu, J.; Wang, D.; Wan, L.-J.; Alvi, S. F.; Li, L. (Angew. Chem., Int. Ed., 2013)

(untitled) - Rao, C. V.; Cabrera, C. R.; Ishikawa, Y. (J. Phys. Chem. Lett., 2010)

(untitled) - Xing, T.; Zheng, Y.; Li, L. H.; Cowie, B. C. C.; Gunzelmann, D.; Qiao, S. Z.; Huang, S.; Chen, Y. (ACS Nano, 2014)

(untitled) - Morais, R. G.; Rey-Raap, N.; Figueiredo, J. L.; Pereira, M. F. R. (Beilstein J. Nanotechnol., 2019)

(untitled) - Sakaushi, K.; Eckardt, M.; Lyalin, A.; Taketsugu, T.; Behm, R. J.; Uosaki, K. (ACS Catal., 2018)

(untitled) - Eckardt, M.; Sakaushi, K.; Lyalin, A.; Wassner, M.; Hüsing, N.; Taketsugu, T.; Behm, R. J. (Electrochim. Acta, 2019)

(untitled) - Kim, H.; Lee, K.; Woo, S. I.; Jung, Y. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Roldán, L.; Armenise, S.; Marco, Y.; García-Bordejé, E. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Xue, Y.; Wu, B.; Jiang, L.; Guo, Y.; Huang, L.; Chen, J.; Tan, J.; Geng, D.; Luo, B.; Hu, W.; Yu, G.; Liu, Y. (J. Am. Chem. Soc., 2012)

(untitled) - Gutiérrez-Pardo, A.; Ramírez-Rico, J.; Cabezas-Rodríguez, R.; Martínez-Fernández, J. (J. Power Sources, 2015)

(untitled) - Nettelroth, D.; Schwarz, H.-C.; Burblies, N.; Guschanski, N.; Behrens, P. (Phys. Status Solidi A, 2016)

(untitled) - Tang, J.; Liu, J.; Torad, N. L.; Kimura, T.; Yamauchi, Y. (Nano Today, 2014)

(untitled) - Wassner, M.; Eckardt, M.; Gebauer, C.; Bourret, G. R.; Hüsing, N.; Behm, R. J. (Electrochim. Acta, 2017)

(untitled) - Wassner, M.; Eckardt, M.; Gebauer, C.; Hüsing, N.; Behm, R. J. (ChemElectroChem, 2016)

(untitled) - Romero-Anaya, A. J.; Ouzzine, M.; Lillo-Ródenas, M. A.; Linares-Solano, A. (Carbon, 2014)

(untitled) - Liu, T.; Liu, E.; Ding, R.; Luo, Z.; Hu, T.; Li, Z. (Electrochim. Acta, 2015)

(untitled) - Anton, R. (Carbon, 2009)

(untitled) - Sevilla, M.; Fuertes, A. B. (Chem. – Eur. J., 2009)

(untitled) - Nagaiah, T. C.; Kundu, S.; Bron, M.; Muhler, M.; Schuhmann, W. (Electrochem. Commun., 2010)

(untitled) - Barnakov, C. N.; Khokhlova, G. P.; Malysheva, V. Y.; Popova, A. N.; Ismagilov, Z. R. (Solid Fuel Chem., 2015)

(untitled) - Chi, S.-H.; Kim, G.-C. (J. Nucl. Mater., 2008)

(untitled) - Barbera, K.; Frusteri, L.; Italiano, G.; Spadaro, L.; Frusteri, F.; Perathoner, S.; Centi, G. (Chin. J. Catal., 2014)

(untitled) - Wollbrink, A.; Volgmann, K.; Koch, J.; Kanthasamy, K.; Tegenkamp, C.; Li, Y.; Richter, H.; Kämnitz, S.; Steinbach, F.; Feldhoff, A.; Caro, J. (Carbon, 2016)

(untitled) - Malard, L. M.; Pimenta, M. A.; Dresselhaus, G.; Dresselhaus, M. S. (Phys. Rep., 2009)

(untitled) - Dresselhaus, M. S.; Dresselhaus, G.; Saito, R.; Jorio, A. (Phys. Rep., 2005)

(untitled) - Reich, S.; Thomsen, C. (Philos. Trans. R. Soc., A, 2004)

(untitled) - Kawashima, Y.; Katagiri, G. (Phys. Rev. B, 1995)

(untitled) - Kaufman, J. H.; Metin, S.; Saperstein, D. D. (Phys. Rev. B, 1989)

Handbook of X-ray Photoelectron Spectroscopy - Moulder, J. F.; Stickle, W. F.; Sobol, P. E.; Bomben, K. D. (Perkin Elmer Corp., 1992)

(untitled) - Schmidt, T. J.; Gasteiger, H. A.; Stäb, G. D.; Urban, P. M.; Kolb, D. M.; Behm, R. J. (J. Electrochem. Soc., 1998)